2020
DOI: 10.1111/jcmm.15238
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced liver but not muscle OXPHOS in diabetes and reduced glucose output by complex I inhibition

Abstract: Mitochondrial function is critical in energy metabolism. To fully capture how the mitochondrial function changes in metabolic disorders, we investigated mitochondrial function in liver and muscle of animal models mimicking different types and stages of diabetes. Type 1 diabetic mice were induced by streptozotocin (STZ) injection. The db/db mice were used as type 2 diabetic model. High‐fat diet‐induced obese mice represented pre‐diabetic stage of type 2 diabetes. Oxidative phosphorylation (OXPHOS) of isolated m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 43 publications
2
13
0
1
Order By: Relevance
“…Mitochondrion is a cell organelle responsible for aerobic metabolism such as tricarboxylic acid cycle and oxidative phosphorylation (OXPHOS). Our previous research and some other studies have revealed that liver mitochondrial function enhanced in obese and diabetic mice [13][14][15], while BBR was able to reduce oxygen consumption of hepatocytes in vitro as well as enhance glucose consumption via inducing glycolysis [16][17][18]. And evidences including ours also confirmed that BBR inhibited complex I function [17,[19][20][21].…”
Section: Introductionsupporting
confidence: 76%
“…Mitochondrion is a cell organelle responsible for aerobic metabolism such as tricarboxylic acid cycle and oxidative phosphorylation (OXPHOS). Our previous research and some other studies have revealed that liver mitochondrial function enhanced in obese and diabetic mice [13][14][15], while BBR was able to reduce oxygen consumption of hepatocytes in vitro as well as enhance glucose consumption via inducing glycolysis [16][17][18]. And evidences including ours also confirmed that BBR inhibited complex I function [17,[19][20][21].…”
Section: Introductionsupporting
confidence: 76%
“… Zhang et al (2011) observed a significant reduction in CIII activity of the ETC in the kidney of diabetic mice, accompanied by an overactivity of CI. Alimujiang et al (2020) also demonstrated increased CI and CII activity of the ETC in the liver of streptozotocin-induced diabetic rats.…”
Section: Discussionmentioning
confidence: 77%
“…Male mice aged 6–8 weeks old were used and fed with a normal chow diet (4% fat, 3.85 kcal/g, 1010010; Jiangsu Synergistic Medicine Bioengineering Co., Ltd., Jiangsu, China) or with high-fat diet (HFD; 60% fat, 5.24 kcal/g, D12492; Research Diets, Inc., New Brunswick, NJ, United States) for 12 weeks. The intraperitoneal glucose tolerance test (IPGTT) and the intraperitoneal insulin tolerance test (IPITT) were performed as previously described with some modifications ( Alimujiang et al, 2020 ). For IPGTT, the mice were intraperitoneally injected with glucose (1.5 g/kg body weight) after overnight fasting.…”
Section: Methodsmentioning
confidence: 99%
“…Murine primary hepatocytes and Kupffer cells were isolated using the two-step perfusion method as previously described with some modifications ( Park et al, 2017 ; Alimujiang et al, 2020 ). Mice were anesthetized and then sequentially perfused with a calcium-free solution and a collagenase IV solution until the liver was completely digested.…”
Section: Methodsmentioning
confidence: 99%